Produksi: Telaah Pemikiran Muhammad Abdul Mannan Dalam Ekonomi Islam (Studi Kasus Produksi Garam Rakyat Madura) - Iwan Hidayat (ITB AAS INDONESIA Surakarta, 2021)
Production is the provision of goods and services with due regard to the value of justice and benefit to society. Production also has an important role in determining the standard of human life and the prosperity of a nation. In this study, the focus is on salt production in Madura. Salt is a white solid object in the form of crystals which is a collection of compounds with the largest portion of sodium chloride (NaCl) and other compounds such as Magnesium Chloride, Magnesium Sulfate, Calcium Chloride, etc. Broadly speaking, Islamic economics is a science that studies human behavior in an effort to meet needs with limited means of fulfilling needs within the framework of Islamic Sharia. The approach used is a qualitative approach with the type of case study research, namely research on humans (can be a group, and individuals), events, settings in depth. As well as data collection techniques are observation, interviews and documentation. This case study is very relevant and is in line with the use of a modern tool in the use of salt production in Madura, the first to increase production and improve the quality of Madurese and national salt. The emphasis is on quality, quantity, maximization and participation in the production process which provides different functions in the production process